APLIKASI REGULASI PEMBINAAN ANAK JALANAN OLEH DINAS SOSIAL DAN PENANGGULANGAN KEMISKINAN KOTA BANDUNG - Arifani, Moh. Anif; Sari, Avid Leonardo; Rifkah, Rifkah (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
The problem of street children in the city of Bandung is no stranger to the people of Bandung. Moreover, the emergence of street children is caused due to family poverty. They survive in various ways such as singing, shining shoes, selling newspapers, begging and so on. Not infrequently the street children to commit crimes such as pickpocketing, stealing because of being pressured by economic circumstances. In this study, the authors used qualitative methods to reveal more in-depth, how the implementation of Law No. 23 of 2002 on the protection of children in the development of street children in the Department of Social Welfare and Poverty Bandung, which handles these street children. While the descriptive analysis of data collected through interviews with key informants and ordinary informants are not structured or open.